Efforts To Increase The Learning Outcomes Of Biology Through The Methods Of Cooperative Learning Type Group Investigation - Kurnia Putra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This study aims to improve student learning outcomes through the implementation of cooperative learning Group Investigation. This research is a classroom action research (Classroom Action Research) conducted in two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. The subject of the research is all students as much as 352 students of VII-1 to VII-10 SMP Negeri 1 Rantau Utara, while its object is the students of class VII-1 as many as 34 students. The research Data is obtained through the provision of test, questionnaire, observation, and interview. The technique of data analysis is the technique of cooperative. The results showed increase in the percentage of student learning outcomes based on the test in the classical style for the initial test of 00,00% (category have not yet succeeded), the first cycle of 52,94% (category have not yet managed) and cycle II 91,18% (the category of work), which indicates an increase. The conclusion from this research is that the implementation of cooperative learning Group Investigation can improve the ability of learning outcomes biology class VII-1 SMP Negeri 1 Rantau Utara